2010
DOI: 10.1523/jneurosci.1312-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

The DREAM Protein Negatively Regulates the NMDA Receptor through Interaction with the NR1 Subunit

Abstract: Glutamate-induced excitotoxicity has been implicated in the etiology of stroke, epilepsy, and neurodegenerative diseases. NMDA receptors (NMDARs) play a pivotal role in excitotoxic injury; however, clinical trials testing NMDAR antagonists as neuroprotectants have been discouraging. The development of novel neuroprotectant molecules is being vigorously pursued. Here, we report that downstream regulatory element antagonist modulator (DREAM) significantly inhibits surface expression of NMDARs and NMDAR-mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
81
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 47 publications
(55 reference statements)
0
81
0
Order By: Relevance
“…DREAM/KChIP3 also binds to the amino-terminal portion of Ca 2ϩ -activated Kv4 potassium channels, which are highly expressed in the brain and heart and contribute to the transient, voltage-dependent potassium ion currents (A-currents) in the nervous system and the transient outward currents in the heart (15,16). DREAM also modulates signaling of the N-methyl-D-aspartate membrane receptor (17 …”
mentioning
confidence: 99%
“…DREAM/KChIP3 also binds to the amino-terminal portion of Ca 2ϩ -activated Kv4 potassium channels, which are highly expressed in the brain and heart and contribute to the transient, voltage-dependent potassium ion currents (A-currents) in the nervous system and the transient outward currents in the heart (15,16). DREAM also modulates signaling of the N-methyl-D-aspartate membrane receptor (17 …”
mentioning
confidence: 99%
“…The repression of gene transcription by DREAM-DRE promoter element interaction is abolished when intracellular free Ca 2+ is elevated [1,2]. Using transgenic mice (TgDREAM) overexpressing a Ca 2+ -and cAMP-insensitive DREAM mutant it was found that NMDA receptor-mediated synaptic transmission and plasticity was impaired in TgDREAM mice [27,28]. Zaidi et al [29] have found that calsenilin traslocates from the cytoplasm to the nucleus when cells were treated with pharmacological agents that directly manipulate the levels of intracellular calcium (caffeine and the calcium ionophore A23187), suggesting that the increased levels of calsenilin in the nucleus are mediated by changes in the intracellular calcium concentration [29].…”
Section: Discussionmentioning
confidence: 99%
“…S421A mutation significantly reduced surface D1R (t 2 ¼ 5.8, po0.05), whereas no significant difference of the total levels of D1R and S421A-D1R was detected (Figure 2b). Tat-mediated intracellular delivery of functional peptides is an effective intervention method that has been proved by us and others (Futaki, 2005;Ji et al, 2006;Zhang et al, 2010). Thus, we constructed a Tat-S421 peptide (Figure 2c, top) to competitively inhibit the phosphorylation of D1R on S421.…”
Section: Pkd1 Contributes To Cocaine-induced Locomotor Hyperactivity mentioning
confidence: 99%